Optimal time interval between neoadjuvant chemoradiotherapy and surgery for rectal cancer. Issue 7 (27th March 2013) - Sloothaak, D. A. M.; Geijsen, D. E.; van Leersum, N. J.; Punt, C. J. A.; Buskens, C. J.; Bemelman, W. A.; Tanis, P. J.; ,
<x xml:space="preserve">Abstract</x> Background Neoadjuvant chemoradiotherapy (CRT) has been proven to increase local control in rectal cancer, but the optimal interval between CRT and surgery is still unclear. The purpose of this study was to analyse the influence of variations in clinical practice regarding timing of surgery on pathological response at a population level. Methods All evaluable patients who underwent preoperative CRT for rectal cancer between 2009 and 2011 were selected from the Dutch Surgical Colorectal Audit. The interval between radiotherapy and surgery was calculated from the start of radiotherapy. The primary endpoint was pathological complete response (pCR; pathological status after chemoradiotherapy (yp) T0 N0). Results A total of 1593 patients were included. The median interval between radiotherapy and surgery was 14 (range 6–85, interquartile range 12–16) weeks. Outcome measures were calculated for intervals of less than 13 weeks (312 patients), 13–14 weeks (511 patients), 15–16 weeks (406 patients) and more than 16 weeks (364 patients). Age, tumour location and R0 resection rate were distributed equally between the four groups; significant differences were found for clinical tumour category (cT4: 17·3, 18·4, 24·5 and 26·6 per cent respectively; P = 0·010) and clinical metastasis category (cM1: 4·4, 4·8, 8·9 and 14·9 per cent respectively; P < 0·001). Resection 15–16 weeks after the start of CRT resulted in the highest pCR rate (18·0 per cent; P = 0·013), with an independent association (hazard ratio 1·63, 95 per cent confidence interval 1·20 to 2·23). Results for secondary endpoints in the group with an interval of 15–16 weeks were: tumour downstaging, 55·2 per cent (P = 0·165); nodal downstaging, 58·6 per cent (P = 0·036); and (near)‐complete response, 23·2 per cent (P = 0·124). Conclusion Delaying surgery until the 15th or 16th week after the start of CRT (10–11 weeks from the end of CRT) seemed to result in the highest chance of a pCR.